Senegal - Urban Development and Decentralization Program - Farvacque-Vitkovic, Catherine D. (World Bank, Washington, DC, 2012)
The Senegal - Urban Development and Decentralization Program provided a credit of $75 million and was implemented over the years 1998-2004. It had 4 development objectives: (i) improve the financial and organizational management of municipalities; (ii) improve the programming of priority urban investments; (iii) rationalize and simplify the financing of urban investments; and (iv) upgrade basic infrastructure in urban and some rural communities. The project addressed the gap between the capacity of local governments and the expectations of the new regulatory and institutional framework. It covered all the country's municipalities and became the backbone of Senegal's decentralization program. At the project's outset, the financial and organizational management of the Senegalese municipalities was known to be weak, but little information existed about the situation in each municipality. No investment programming had been carried out to reflect their priority needs and capacity to finance them. The project also recognized that funding allocations were not being made fairly or transparently. All four development objectives were fully achieved cost-effectively and sustainably.